Introduction: museums and material religion - Paine, Crispin (Material religion, 2012)
Dramatic changes in global cultural politics are one of the sources of a new academic concern with religion in museums, and a new concern by museums to treat with religion. In this issue Brooks, Buggeln, O'Neill, and Goa address four different aspects of this new turn; when brave enough to address the great questions of meaning, museums can sometimes reach the human heart.